Residents’ perceptions of the visual quality of on-site wastes storage bins in Kuching. - Chung, Darylynn Yiu Li; Muda, Azizi; Che Omar, Che musa; Abd Manaf, Latifah (Elsevier, 2010)
Concerns regarding public health and aesthetics considerations of the on-site waste storage have arisen due to improper storage of waste. Research on resident's visual preferences and concerns for solid waste management facilities is still limited. Therefore, the goal of this study is to understand the perceived visual aesthetic quality of on-site waste storage facilities in Kuching, Sarawak. Since the privatization of solid waste management in Kuching, the concessionaire has been providing uniform mobile garbage bins to residents. This has improved the solid waste management systems. Photographs showing the mobile garbage bins provided by the concessionaire have the highest ratings.